(untitled) (Global Journal of Medical Research, 2022)
The Aids is a pathology with high incidence in the teenagers, once the manifestation occurs between seven to ten years after the infection, said that this is the incubation period. Despite the emergence in the late 80 years in the United Estates, there is no cure, having only treatment and prophylaxis, so the APS and SUS playing the important role in this issue. Since it is a pathology that affects the immune system, its evolution has several variants, since each person#x2019;s organism functioned differently at the same stimuli. The clinical consequences of HIV infection range from acute syndrome associated with primary infection to a prolonged asymptomatic phase culminating in advanced disease. (KASPER et al, 2013) Treatment is carried out based on antiretroviral medicinal products (ARS), with the intention of prolonging survival and improving quality of life by reducing viral load and reconstitution of the individual#x2019;s immune system. Research was carried out on an online platform such as Google Scholar, Scielo, BVS, with the intention of exposing the necessary aspects for the population to understand about the diagnostic, manifestation of the disease, treatment, prophylaxis and the primary care.